2007
DOI: 10.2106/jbjs.f.00007
|View full text |Cite
|
Sign up to set email alerts
|

Structural Integrity and Clinical Outcomes After Arthroscopic Repair of Isolated Subscapularis Tears

Abstract: Therapeutic Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
264
3
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(301 citation statements)
references
References 16 publications
13
264
3
8
Order By: Relevance
“…Although magnetic resonance imaging (MRI) has shown to be a useful tool for the diagnosis of supraspinatus and infraspinatus tendon tears,[16] we believe that subscapularis tendon tears are more difficult to recognize and are therefore underestimated. The prevalence of subscapularis tendon tears has not been widely studied,[78] and only a few authors have classified them. [79] To the best of our knowledge, no study to date has compared MRI findings with arthroscopic findings based on the same classification.…”
Section: Introductionmentioning
confidence: 99%
“…Although magnetic resonance imaging (MRI) has shown to be a useful tool for the diagnosis of supraspinatus and infraspinatus tendon tears,[16] we believe that subscapularis tendon tears are more difficult to recognize and are therefore underestimated. The prevalence of subscapularis tendon tears has not been widely studied,[78] and only a few authors have classified them. [79] To the best of our knowledge, no study to date has compared MRI findings with arthroscopic findings based on the same classification.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the incidence rate of subscapularis tendon tear was 5.4% to 49.4% [2,6,8], and hyper-extension and hyper-external rotation forces by a direct force, sports injuries, and traffic accidents were reported as the injury mechanisms [1,9,18]. Gerber et al reported on a series of sixteen patients with isolated subscapularis repairs who were followed for a minimum of two years.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that 18.7% of patients had required arthroscopic release because of deficit of external rotation of at least 30° [9]. It has been reported that the range of motion of external rotation is restricted after the repair of the subscapularis tendon tear [3,8], but no previous studies have investigated in detail how the difference in the size of full thickness subscapularis tendon tear affects glenohumeral joint motion after the repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Full-thickness subscapularis tears are classically described as types II to V according to Lafosse et al 21 A type II is a full thickness tear of the superior one-third of the tendon. A type III tear includes the superior two-thirds.…”
Section: Type B: Full Thickness Tendon Lesionmentioning
confidence: 99%